Targeting DCLK1 attenuates tumor stemness and evokes antitumor immunity in triple-negative breast cancer by inhibiting IL-6/STAT3 signaling - Heshu Liu; Rui Yan; Zeru Xiao; Xuying Huang; Jiannan Yao; Jian Liu; Guangyu An; Yang Ge (Breast Cancer Research, 2023)
Abstract Triple-negative breast cancer (TNBC) exhibits the poorest outcomes among breast cancer subtypes due to the high heterogeneity and a lasting scarcity of effectual treatments. Targeted therapies based on molecular subtypes of TNBC are critical step toward tailoring treatments to improve clinical outcomes. Gastrointestinal cancer stem cell (CSC) marker DCLK1 was reported to be highly expressed in stem cell-rich subtype of TNBC. Here, we firstly explored the impacts of DCLK1 on tumor cells as well as their immune microenvironment in TNBC and potential therapeutic strategies for TNBC patients with high DCLK1 expression. Our results disclosed that DCLK1 overexpression promoted, while knockout of DCLK1 suppressed the CSC-like traits of TNBC cells and resistance to chemotherapeutics. Besides, DCLK1 supported immune escape by inhibiting intratumoral cytotoxic T cell infiltration in TNBC and hence limited immune checkpoint inhibitors efficacy. Mechanistically, bioinformatics analysis revealed that IL-6/STAT3 signaling was significantly enriched in high DCLK1-expressing patients, and our results further revealed that DCLK1 enhanced IL-6 expression and STAT3 activation in TNBC cells, which finally gave rise to upregulated CSC traits and suppressed CD8+ T-cell activity. Inhibiting IL-6/STAT3 pathway by IL-6R antagonist, Tocilizumab or STAT3 inhibitor, S31-201 could abolish DCLK1-promoted malignant phenotypes of TNBC cells. Finally, DCLK1 was identified to be specifically and highly expressed in the mesenchymal-like subtype of TNBC and targeting DCLK1 could improve chemotherapy efficacy and activate antitumor immunity. Overall, our study revealed the potential clinical benefits of targeting DCLK1 in TNBC treatment.